Exploring the impact of IoT on library collection management efficiency: a literature review - Pamungkas, Damar Nur Satria; Sofiyani, Zulfatun; Hamidon, Huda; Md Arifin, Noor Arina; Abu Bakar, Normashidayu (Faculty of Information Management, 2025)
The emergence of the Internet of Things (IoT) has brought massive changes in various sectors, particularly in library collection management. This paper discusses the impact of IoT on enhancing the efficiency of library collection management practices. By integrating IoT technologies such as Radio Frequency Identification (RFID), smart sensors, and cloud computing, libraries can achieve greater operational efficiency, better accessibility, and stronger security. These technologies facilitate real-time data collection and analysis, streamline inventory management, and automate circulation processes, resulting in increased user engagement and higher service quality. However, implementing IoT comes with challenges, including the need for large investments in security, staff training, and technology infrastructure. This review aims to provide a comprehensive analysis of the benefits and challenges associated with IoT integration in libraries, with a special focus on Indonesian libraries. Research findings indicate that while IoT offers significant advantages in modernizing library services, careful planning and resource allocation are essential to overcome the associated barriers. Future research directions are proposed to further explore the potential of IoT in transforming library operations and enhancing service delivery.